Perancangan Video Pembelajaran 3D Modeling Berbasis Schoology Untuk Mahasiswa DKV Ma Chung - Daniel Chandra Kurniawan; Sultan Arif Rahmadianto; Didit Prasetyo Nugroho (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2022)
Today the world is entering the era of the 4.0 industrial revolution, where technology has become a part of human life. In the world of education, the rapid development of internet and technology encourages renewal efforts in learning. The problem identified one of them is the study of 3D modeling DKV Ma Chung is still conventional and has not adapted the learning in the era of the 4.0 industrial revolution. The method used is Research and Development with an ADDIE version development research model. The steps are: Analysis, Design, Development, and Implementation. The stages of development using stages in video production are pre production, production, and post production. The final result of the study was a Schoology-based 3D modeling learning video product for DKV Ma Chung students. Product eligibility can be seen from the material expert assessment results with a percentage of 85% which is categorized as highly feasible. The results of the media experts with a percentage rate of 88% are categorized as highly feasible. Product ratings by students get a percentage of 88% which is categorized very well.